The Impact of Aesthetic Evaluation and Physical Ability on Dance Perception - Cross, Emily S.; Kirsch, Louise; Ticini, Luca F.; Schütz-Bosbach, Simone (Frontiers in Human Neuroscience, 2011)
The field of neuroaesthetics attracts attention from neuroscientists and artists interested in the neural underpinnings of aesthetic experience. Though less studied than the neuroaesthetics of visual art, dance neuroaesthetics is a particularly rich subfield to explore, as it is informed not only by research on the neurobiology of aesthetics, but also by an extensive literature on how action experience shapes perception. Moreover, it is ideally suited to explore the embodied simulation account of aesthetic experience, which posits that activation within sensorimotor areas of the brain, known as the action observation network (AON), is a critical element of the aesthetic response. In the present study, we address how observers’ aesthetic evaluation of dance is related to their perceived physical ability to reproduce the movements they watch. Participants underwent functional magnetic resonance imaging while evaluating how much they liked and how well they thought they could physically replicate a range of dance movements performed by professional ballet dancers. We used parametric analyses to evaluate brain regions that tracked with degree of liking and perceived physical ability. The findings reveal strongest activation of occipitotemporal and parietal portions of the AON when participants view movements they rate as both aesthetically pleasing and difficult to reproduce. As such, these findings begin to illuminate how the embodied simulation account of aesthetic experience might apply to watching dance, and provide preliminary evidence as to why some people find enjoyment in an evening at the ballet.